Instinct [compact disc, unabridged] : the power to unleash your inborn drive - Jakes, T. D. (Hachette Audio, 2014)
Outlines how to re-discover one's natural aptitudes and re-claim the wisdom of past experiences to become in sync with the opportunities life offers.